A comparative analysis of ante- and postnatal clinical characteristics of extremely premature neonates suffering from refractory and non-refractory hypotension: Is early clinical differentiation possible?. (October 2017) - Verma, Rita P.; Dasnadi, Shaeequa; Zhao, Yuan; Chen, Hegang H.
Abstract: Background: About 25% of hypotensive ELBW infants are refractory to intravascular volume expansion and inotropic drugs (VI) and require hydrocortisone (HC). Such neonates suffer from complications of prolonged hypotension and extended therapy with VI. ELBW infants with refractory hypotension (RH) are clinically and biochemically indistinguishable from those who respond to VI. Objective: Early identification and differentiation of ELBW infants susceptible to steroid dependent hypotension from those who respond to inotropic medications. Methods: In a retrospective study the ante- and postnatal clinical characteristics of ELBW infants who received hydrocortisone (HC) for refractory hypotension (RH) were compared to those who responded to volume-inotropes (VI). Results: Infants in HC group had lower birth weight (BW, 675 ± 121 g) and gestational age (GA, 25.1 ± 1.3 weeks) and higher mean airway pressure and oxygen requirements, all independent of antenatal steroid (ANS) exposure. The receipt of ANS (p 0.01) and occurrences of maternal diabetes mellitus (GDM, p 0.01) were lower in HC group. ANS (OR 0.5, 95% CI 0.2–0.9, p 0.01) and GDM (OR 0.3, 95% CI 0.09–0.9, p 0.04) reduced the risk for RH. HC group had higher risk for IVH (OR 2.1, 95% CI 1.02–4.2 p = 0.04) which declined in the multivariate analysis. A trend towards lower risk of ventriculomegaly (VM) was noted in HC group (OR 0.3, 95% CI 0.1–1.1), which became significant after controlling for BW (OR 0.2 95% CI 0.07–0.9, p 0.04). Similar trend was noted for maternal hypertension. Conclusion: Hypotension in ELBW infants who are ≤ 25 wks of GA and unexposed to ANS and GDM is refractory to VI therapy. Such neonates may benefit from an initial therapy with, or earlier institution of hydrocortisone. The trend towards a higher risk for VM with VI therapy needs validation in future studies.